The role of art education in adult prisons: The Western Australian experience - Giles, M.; Paris, Lisa; Whale, J. (Springer Netherlands, 2016)
Incarceration costs are high; in Australia, for example, each prisoner costs an average of AUD 115,000 per year. Other countries are also feeling the fiscal pinch of high incarceration costs, and a number of jurisdictions are now closing some of their prisons. Most prison costs are non-discretionary (accommodation, meals, etc.). But some of the costs relate to discretionary activities, services and facilities (including schooling). In terms of correctional education, many prison managers try to invest any meagre correctional education resources available to them in those classes and courses which have proven to have the best results, such as improved labour market outcomes and reduced recidivism, minimising subsequent re-imprisonment. Course offers for prisoner-students include vocational training, adult basic education (ABE) and art studies. The two-tiered question this paper asks is: do art classes and courses produce these measurable outcomes and, if not, are there other reasons why they should continue to be funded? Addressing these issues, the authors argue that (1) these measurable outcomes are too narrow and do not reflect the complex but less quantifiable benefits to the individual and the community of studying art in prison, and (2) better measures of all impacts of art studies in prisons are needed, including qualitative and humanitarian aspects.